The Effect of Web Reinforcement on the Shear Capacity of Brick Aggregate Concrete Beams - Hossain, Md. Monjur; Z. Bosunia, M. Shamim; Ali, Md. Hazrat (Universiti Putra Malaysia Press, 1999)
Shear capacity of reinforced brick aggregate concrete beams without any web reinforcement and with varying ratio of web reinforcement was studied in this investigation. Deflections of beams and cracks during the progress of loading were recorded. Brick aggregate concrete beams with web reinforcement and two layers of tensile reinforcement were found to have increased cracking shear stress by a considerable amount. Equations for cracking and ultimate shear stresses were suggested within the scope of this study. The experimental values of ultimate shear strength of beams were compared with the values obtained by equations proposed by ACI and other researchers. The equations proposed herein were found to represent the test results better than those of other researchers while remaining on the conservative side. It is hoped that the equations developed herein will provide a rational and basic point of departure from the prevailing concept and will help towards the formulation of a suitable code to provide web reinforcement for brick aggregate concrete beams.